Coping as a mediator between locus of control, competence beliefs, and mental health: a systematic review and structural equation modelling meta-analysis - Groth, Nicola; Schnyder, Nina; Kaess, Michael; Markovic, Andjela; Rietschel, Liz; Moser, Susann; Michel, Chantal; Schultze-Lutter, Frauke; Schmidt, Stefanie J. (Behaviour research and therapy, 2019)
OBJECTIVE: This systematic review and two-staged structural equation modelling meta-analysis (TSSEM) aimed to examine whether coping mediates the associations between locus of control, competence beliefs, and mental health in the general population and clinical samples. - METHODS: Eligible studies published until May 2017 were identified through systematic searches of PubMED and EMBASE. The review included 19 studies and the meta-analysis 15 studies. - RESULTS: The review supports the assumption that coping mediates the associations between locus of control and competence beliefs, and mental health. TSSEM using a pooled sample of 3986 respondents and 225 cross-sectional effect sizes indicated that maladaptive coping mediates the association between maladaptive locus of control and mental health problems. On the contrary, adaptive coping did not mediate this association and was only significantly associated with competence beliefs and adaptive locus of control but, unexpectedly, not with mental health. Both maladaptive and adaptive locus of control but not competence beliefs had direct links to mental health problems that were independent of coping. - CONCLUSION: Interventions should not only focus on enhancing adaptive coping as it might be more promising to diminish maladaptive locus of control, which may result in reduced maladaptive coping and, finally, improved mental health.